Optimization of ionic strength of nutrient solution for enhanced hydroponic watermelon yield and quality in greenhouse - Md Mukhtar Hossain; Yuki Shibasaki; Rina Nakao; Kazuki Nitano; Fumiyuki Goto (Scientific Reports)
Abstract Optimizing nutrient solution concentration (NSC) in hydroponic systems is crucial for enhancing nutrient efficiency and maximizing crop growth, yield, and quality. This study evaluated the effects of different NSCs on physiological responses, growth parameters, yield, and quality of watermelon (Citrullus lanatus) in a vertical farming system within a greenhouse in Japan from May to August 2024. Four NSCs were tested: Enshi Shoho (control), Formula-1, Formula-2, and Formula-3. These formulations were based on nutrient absorption rates determined by high-pressure ion chromatography (HPIC) in a preliminary study. The results demonstrated significant variations in vegetative growth, physiological responses, and yield attributes among treatments. Formula-1, with a reduced NSC, exhibited increased leaf area, chlorophyll content, photosynthetic rate, stomatal conductance, transpiration rate, plant fresh weight, and dry weight. It also produced larger ovaries and fruits, increasing yield by 14.8% compared to the control. Additionally, Formula-1 showed higher Brix (12.00), lycopene content, and flesh thickness (154.26 mm), indicating early maturity due to higher sugar and lower acid content. Performance ranking was Formula-1 > Formula-3 > Control > Formula-2. Thus, Formula-1 was identified as the optimal NSC for maximizing watermelon growth, physiological efficiency, yield, and quality in hydroponic cultivation.